Professional activity and professional identity: A cultural-historical investigation into change and transformation in Children’s Services - Paul Wiseman (Educational Futures)
This paper presents the findings of a quasi-longitudinal investigation of the lived experiences of Children’s Service professionals between 2004 and 2012. The aim of the research was to gain an understanding of the factors which shape and transform professional activity. Data collection was undertaken using semi-structured interviews and Cultural Historical Activity Theory (CHAT) was used as the analytical framework. The findings of the research surfaced a number of tensions that were evident within Children’s Services. These included the limited role that government policy took in shaping professional activity together with the need for senior managers to translate national policy into localised practice via clearly articulated strategic vision; as well as the need to develop new ‘Council’ rules to promote new ways of working. The findings also challenged the concept of a stable ‘community of practice’ as proposed by Lave and Wenger and supported Vygotsky’s notion that learning is underpinned by discontinuity, conflict and displacement. Engestrom’s concepts of historicity and multi-voicedness also proved to be particularly applicable to the process of change that took place in and between both phases of the research.